Amorphous Ni0.75Fe0.25(OH)2‐Decorated Layered Double Perovskite Pr0.5Ba0.5CoO3‐δ for Highly Efficient and Stable Water Oxidation. Issue 3 (11th January 2017) - Liang, Fengli; Sunarso, Jaka; Mao, Junkui; Yang, Ziqiong; Zhou, Wei
Abstract: Highly active, durable, and cost‐effective electrocatalysts for water oxidation into oxygen gas hold a key role to realise a range of renewable energy solutions which include water‐splitting and rechargeable metal‐air batteries. Despite its very stable oxygen evolution reaction (OER) performance over large number of cycles, layered double perovskite PrBaCo2 O5+ δ (PBC) has a rather limited surface area. It is, thus, desirable to have the stability of PBC combined with the higher OER activity obtained by enlarging its surface area. Here, we used micro‐sized PBC particles as the substrate for the deposition of nano‐sized nickel‐iron hydroxide, Ni0.75 Fe0.25 (OH)2, which led to an order of magnitude improvement in the OER current density at 1.63 V versus the reversible hydrogen electrode for the amorphous Ni0.75 Fe0.25 (OH)2 ‐decorated PBC catalyst (A‐Ni0.75 Fe0.25 (OH)2 +PBC), relative to the PBC catalyst. We showed that the crystal ordering of the decoration affects the OER activity, that is, the amorphous decoration provided a higher OER activity than the crystalline decoration by enabling a larger contact area between the catalyst and the aqueous electrolyte. The results we show here could potentially stimulate more innovative future works utilising simple chemical preparation route to realise high‐performance hybrid OER catalysts involving novel constituents. Abstract : Keep in contact : Layered double perovskite PrBaCo2 O5+ δ (PBC) is decorated with a series of nano‐sized catalysts, that is, Ni0.75 Fe0.25 (OH)2, Ni(OH)2, Ni0.75 Fe0.25 O, NiO, RuO2, and Ag. The amorphous Ni0.75 Fe0.25 (OH)2 ‐decorated PBC catalyst displays the best oxygen evolution reaction activity and stability in an alkaline medium, even relative to its crystalline Ni0.75 Fe0.25 (OH)2− decorated PBC counterpart, owing to the larger electrolyte‐catalyst contact area for the amorphous decorated catalyst.